TO DETERMINE FETOMATERNAL OUTCOMES IN TERM SINGLETON PREGNANCY WITH OLIGOHYDROAMNIOS - Dr. Ayushri Yadav; Dr. Siddhi Sainik; Dr. Aditi Singh Parihar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- The amniotic fluid is the fluid that collects within the amniotic cavity surrounding the embryo. Amniotic fluid is the fluid that surrounds the embryo within the layer of amniotic sac.Aims- A study of feto-maternal outcomes of oligohydramnios beyond 28 weeks of gestation in a singleton pregnancy.Methods and materials- Present study is a hospital-based study on feto-maternal outcome in term gestation with oligohydramnios in a singleton pregnancy, was carried out in Department of Obstetrics & Gynecology, Peoples College of Medical Sciences and Research Centre, Bhopal, during the period of January 2022 to January -2024. All data entered into tables and charts. Results- The highest no of patients with oligohydramnios in this study were   in the age group of 20-23years. Total number of NICU admissions were 94 babies. 47% fetuses with oligohydramnios had NICU admissions. Maximum patients with oligohydramnios were second gravida. Highest number of patients with oligohydramnios were delivered by LSCS. More number of patients were seen with NST reactivity (62.8%) than   with non-reactivity (37.2%). Maximum number of patients are with a reactive NST -125 patients    compared to 74 patients with non-reactive NST. The mean weight of babies with oligohydramnios in the present study is 2 kgs. 59 patients were with a baby weight of 2kgs. Highest number of babies were born with an average birth weight of  2 kgs. Maximum LSCS in the present study was done for fetal distress (24.5%), followed by CPD (23.8%) and IUGR (18.5%). Maximum number of patients with oligohydramnios were having clear liquor (61.3%) compared to patients with meconium stained liquor (38.7%). Maximum number of patients with oligohydramnios have spontaneous onset of labour (125 patients) compared to patients with induced labour (75 patients) in the present study.Conclusion- From this study, we conclude that oligohydramnios is a high-risk pregnancy and proper antepartum care, intensive fetal surveillance and intrapartum care are required in patient with oligohydramnios. Every case of oligohydramnios needs careful antenatal evaluation, parental counseling, individualization, decisions regarding time and mode of delivery. Continuous intrapartum fetal monitoring and good neonatal care are necessary for better perinatal outcome